Novel Viral Communities Potentially Assisting in Carbon, Nitrogen, and Sulfur Metabolism in the Upper Slope Sediments of Mariana Trench - Jiulong Zhao; Hongmei Jing; Zengmeng Wang; Long Wang; Huahua Jian; Rui Zhang; Xiang Xiao; Feng Chen; Nianzhi Jiao; Yongyu Zhang (mSystems, 2022)
ABSTRACT Viruses are ubiquitous in the oceans. Even in the deep sediments of the Mariana Trench, viruses have high productivity. However, little is known about their species composition and survival strategies in that environment. Here, we uncovered novel viral communities (3,206 viral scaffolds) in the upper slope sediments of the Mariana Trench via metagenomic analysis of 15 sediment samples. Most (99%) of the viral scaffolds lack known viral homologs, and ca. 59% of the high-quality viral genomes (total of 111 with completeness of >90%) represent novel genera, including some Phycodnaviridae and jumbo phages. These viruses contain various auxiliary metabolic genes (AMGs) potentially involved in organic carbon degradation, inorganic carbon fixation, denitrification, and assimilatory sulfate reduction, etc. This study provides novel insight into the almost unknown benthic viral communities in the Mariana Trench. IMPORTANCE The Mariana Trench harbors a substantial number of infective viral particles. However, very little is known about the identity, survival strategy, and potential functions of viruses in the trench sediments. Here, through metagenomic analysis, unusual benthic viral communities with high diversity and novelty were discovered. Among them, 59% of the viruses with a genome completeness of >90% represent novel genera. Various auxiliary metabolic genes carried by these viruses reflect the potential adaptive characteristics of viruses in this extreme environment and the biogeochemical cycles that they may participate in. This study gives us a deeper understanding of the peculiarities of viral communities in deep-sea/hadal sediments.